ACCOUNTING FOR PUBLIC INFRASTRUCTURE ASSETS: CHALLENGES IN VALUATION AND RECOGNITION - Kathleen Asyera Risakotta; Marannu Paledung; Ambarwati Soetiksno (Adisam Publisher, 2025)
The valuation and recognition of public infrastructure assets has become a critical issue in public sector accounting, particularly in the context of government financial transparency and accountability. Infrastructure assets such as roads, bridges, water networks, and other public facilities often possess unique characteristics that distinguish them from ordinary commercial assets, both in terms of their useful lives, maintenance costs, and contribution to public welfare. This study aims to examine the challenges in the valuation and recognition of public infrastructure assets using a literature review method. The review indicates that the main challenges arise from differences in accounting standards across countries, the limited valuation methods that adequately represent the economic and social value of infrastructure assets, and the difficulty in determining useful lives and replacement costs. Furthermore, the debate over whether infrastructure assets should be measured at historical cost or fair value is also a significant issue. This study emphasizes the need for a more adaptive, comprehensive, and public interest-oriented accounting approach to improve the reliability of government financial reports. Therefore, the results of this study can serve as a foundation for developing public sector accounting policies that are more responsive to the complexities of infrastructure management.